2020
DOI: 10.3390/jcm9041080
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Objectively-Assessed Physical Activity and Sedentary Time with Hippocampal Gray Matter Volume in Children with Overweight/Obesity

Abstract: This study investigated physical activity (PA) and sedentary time (SED) in relation to hippocampal gray matter volume (GMV) in pediatric overweight/obesity. Ninety-three children (10 ± 1 year) were classified as overweight, obesity type I, or type II–III. PA was assessed with non-dominant wrist accelerometers. GMV was acquired by magnetic resonance imaging (MRI). Neither PA nor SED associated with GMV in the hippocampus in the whole sample (p > 0.05). However, we found some evidence of moderation by weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 54 publications
2
24
1
Order By: Relevance
“…Leppänen et al 6 also confirmed that higher levels of VPA and MVPA at the age of 4.5 year were associated with improved CRF 12 months later in unadjusted and adjusted models. Lack of significant associations between MVPA at the age of 6.6 year with the number of laps in the 20‐m shuttle run test, after controlling for confounders in our study could be attributed to the method we applied for calculating the average daily values of time spent in the zones of physical activity [(weekdays*5 + weekends*2)/7], 17 since the we run as well the analysis with arithmetic means and found similar associations between MVPA at 6.6 year with later CRF (data not shown) as in the study conducted by Leppänen et al 6 Therefore, we can summarize that particularly a more intensive type of PA is associated with higher CRF in children. In addition, we found out that as opposed to the counteraction of LPA, setting SB as exposure did not attenuate the positive impact of VPA.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Leppänen et al 6 also confirmed that higher levels of VPA and MVPA at the age of 4.5 year were associated with improved CRF 12 months later in unadjusted and adjusted models. Lack of significant associations between MVPA at the age of 6.6 year with the number of laps in the 20‐m shuttle run test, after controlling for confounders in our study could be attributed to the method we applied for calculating the average daily values of time spent in the zones of physical activity [(weekdays*5 + weekends*2)/7], 17 since the we run as well the analysis with arithmetic means and found similar associations between MVPA at 6.6 year with later CRF (data not shown) as in the study conducted by Leppänen et al 6 Therefore, we can summarize that particularly a more intensive type of PA is associated with higher CRF in children. In addition, we found out that as opposed to the counteraction of LPA, setting SB as exposure did not attenuate the positive impact of VPA.…”
Section: Discussionmentioning
confidence: 66%
“…Total awake wear time (AWT) was calculated as the sum of SB, LPA, MPA, and VPA 6 . The average daily values of time spent in each PA zone were calculated as (weekdays*5 + weekends*2)/7 17 …”
Section: Methodsmentioning
confidence: 99%
“…Physical activity, sedentary behavior, and sleep have been associated with gray matter volume in specific brain areas, which may explain, in part, their associations with academic achievement, executive function, and intelligence 10‐14 . In children with overweight/obesity, we found a moderator effect of weight status on the association of physical activity and gray matter volume in the hippocampus 12 . Additionally, Esteban‐Cornejo et al found that cardiorespiratory fitness (which can be effectively modified through physical activity) is associated with gray matter volume in seven different brain regions important for academic achievement (eg, premotor cortex, supplementary motor cortex and hippocampus) 11 .…”
Section: Introductionmentioning
confidence: 62%
“…Physical activity, sedentary behavior, and sleep have been associated with gray matter volume in specific brain areas, which may explain, in part, their associations with academic achievement, executive function, and intelligence 10‐14 . In children with overweight/obesity, we found a moderator effect of weight status on the association of physical activity and gray matter volume in the hippocampus 12 .…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation